Angiotensin‐(1‐7) mitigated angiotensin II‐induced abdominal aortic aneurysms in apolipoprotein E‐knockout mice. (2nd March 2020) - Xue, Fei; Yang, Jianmin; Cheng, Jing; Sui, Wenhai; Cheng, Cheng; Li, Hongxuan; Zhang, Meng; Zhang, Jie; Xu, Xingli; Ma, Jing; Lu, Lin; Xu, Jinfeng; et al.
Abstract : Background and Purpose: To test the hypothesis that angiotensin‐(1‐7) [Ang‐(1‐7)] may attenuate abdominal aortic aneurysm (AAA) via inhibiting vascular inflammation, extracellular matrix degradation, and smooth muscle cell (SMC) apoptosis, an animal model of AAA was established by angiotensin II (Ang II) infusion to apolipoprotein E‐knockout (ApoE ‐/‐ ) mice. Experimental Approach: All mice and cultured SMCs or macrophages were divided into control, Ang II‐treated, Ang II + Ang‐(1‐7)‐treated, Ang II + Ang‐(1‐7) + A779‐treated and Ang II + Ang‐(1‐7) + PD123319‐treated groups respectively. In vivo, aortic mechanics and serum lipids were assessed. Ex vivo, AAA were examined by histology, immunohistochemistry and zymography. Cultured cells were analysed by RT‐PCR, western blots and TUNEL assays. Key Results: In vivo, Ang‐(1‐7) reduced the incidence and severity of AAA induced by Ang II infusion, by inhibiting macrophage infiltration, attenuating expression of IL‐6, TNF‐α, CCL2 and MMP2, and decreasing SMC apoptosis in abdominal aortic tissues. Addition of A779 or PD123319 reversed Ang‐(1‐7)‐mediated beneficial effects on AAA. In vitro, Ang‐(1‐7) decreased expression of mRNA for IL‐6, TNF‐α, and CCL2 induced by Ang II in macrophages. In addition, Ang‐(1‐7) suppressed apoptosis and MMP2 expression and activity in Ang II‐treated SMCs. These effects were accompanied by inhibition of the ERK1/2 signalling pathways via Ang‐(1‐7) stimulation of Mas and AT2 receptors. Conclusion and Implications: Ang‐(1‐7) treatment attenuated Ang II‐induced AAA via inhibiting vascular inflammation, extracellular matrix degradation, and SMC apoptosis. Ang‐(1‐7) may provide a novel and promising approach to the prevention and treatment of AAA.